Modulação de Irisina, composição corporal, e parâmetros metabólicos em ratos Wistar obesos exógenos frente ao protocolo de treinamento aeróbico e/ou intervenção dietética - Furino, Vanessa de Oliveira (2021)
Obesity is a disease characterized by the expansion of adipose tissue, which promotes the secretion of factors that lead to comorbidities, such as diabetes and cardiovascular disease. In this sense, dietary intervention and physical exercise have been proposed as strategies to alleviate these complications. Thus, this work aimed to determine the modulation of irisin/FNDC5, biochemical markers and visceral depots in response to dietary intervention and training. For this purpose, Wistar rats were fed a high-fat diet (HFD) for 8 weeks to induce obesity. From the 8th week, the animals were divided into 4 groups: HFD-Ex: trained high-fat diet group; HFD-Sed: sedentary high-fat diet group; CD-Ex: trained chow-diet group; CD-Sed: sedentary chow-diet group. The trained groups were submitted to aerobic exercise on a treadmill for 4-8 weeks, 3x/week, for 60 minutes. At the end of the protocol, serum, liver, pancreas, adipose tissues were collected: MES (mesenteric), EPI (epididymal), RET (retroperitoneal) and brown (TAM) and the gastrocnemius, soleus and extensor digitorum longus (EDL). The area and diameter of visceral depots and hepatic steatosis were determined by analysis of histological slides. Body mass (BM), percentage of body fat (%BF), body area (BA), fat-free mass (FFM), fat mass (FM), bone mineral density (BMD) were determined by DXA. Serum concentrations of IL-1β, IL-10, leptin and irisin were determined by ELISA. The HDL, triglycerides (TG), blood glucose, insulin and HOMA-IR were determined. The expression of FNDC5 protein in the gastrocnemius muscle was evaluated by Western blotting. Our results showed that the high-fat diet promoted the obese phenotype in 8 weeks by increasing the BM, %BF, FM, EPI, RET and MES, blood glucose and irisin. After 4 weeks, dietary intervention was the most important factor in reducing BM, %BF and FM, leptin and glycemia, with no effects on irisin and IL-10, but it increased FNDC5. Furthermore, the effects were maintained after 8 weeks. Physical training also attenuated the disorders arising from obesity, but the changes were more evident after 8 weeks, through the reduction of EPI, RET and MES and IL-1β. However, the expression of FNDC5 and irisin were reduced. The combination of interventions showed similar responses to dietary intervention, after 4 and 8 weeks. Furthermore, visceral depots responded differently, and EPI mass was modulated by all interventions only after 8 weeks. The adipocyte area of EPI, MES and RET were significantly reduced due to the combination of interventions. In general, dietary intervention promotes greater effects than physical training on general parameters associated with visceral adiposity and body composition, while physical exercise acts to prevent the decline in muscle mass. Finally, the combination of aerobic training and dietary intervention results in a tendency to potentiate the effects of interventions, especially in decreasing visceral adiposity. Furthermore, we emphasize that irisin can be used as a biochemical marker of obesity and FNDC5 as a potential indicator of sarcopenic obesity.